ZAKAT DALAM MENDORONG PERTUMBUHAN EKONOMI DAN PENGENTASAN KEMISKINAN - Abdul Haris Romdhoni (ITB AAS INDONESIA Surakarta, 2017)
This study aims to analyze empirically whether zakat has an impact on efforts to reduce the level of poverty. As the main problem faced by the Indonesian people is the problem of poverty. From several analysis results show that zakat can reduce the number and percentage of poor families, and reduce the depth and severity of poverty. The results revealed that the provision of productive zakat capital in the form of business capital has a positive impact and can reduce the poverty rate. Therefore, the provision of productive zakat in the form of venture capital can be continued and upgraded.In addition to the need to develop the distribution of zakat to micro small medium enterprises (SMEs) or group of joint ventures (KUBE) so that there is collaboration and synergy between individuals. Based on the results of the study there is a positive influence between the utilization of productive zakat programs LAZ An-Naafi 'Boyolali to income mustahiq. That income mustahiq influenced by the utilization of productive zakat with a large contribution of influence is 30.5%. This can be seen from the development of income and fulfillment needs mustahiq after following the program of productive zakat empowerment LAZ An-Naafi 'Boyolali which can also be used for venture capital.